Analysis of IgG kinetic stability by differential scanning calorimetry, probe fluorescence and light scattering - Nemergut, Michal (Protein Sci, 2017)
Monoclonal antibodies of the immunoglobulin G (IgG) type have become mainstream therapeutics for the treatment of many life‐threatening diseases. For their successful application in the clinic and a favorable cost‐benefit ratio, the design and formulation of these therapeutic molecules must guarantee long‐term stability for an extended period of time. Accelerated stability studies, e.g., by employing thermal denaturation, have the great potential for enabling high‐throughput screening campaigns to find optimal molecular variants and formulations in a short time. Surprisingly, no validated quantitative analysis of these accelerated studies has been performed yet, which clearly limits their application for predicting IgG stability. Therefore, we have established a quantitative approach for the assessment of the kinetic stability over a broad range of temperatures. To this end, differential scanning calorimetry (DSC) experiments were performed with a model IgG, testing chaotropic formulations and an extended temperature range, and they were subsequently analyzed by our recently developed three‐step sequential model of IgG denaturation, consisting of one reversible and two irreversible steps. A critical comparison of the predictions from this model with data obtained by an orthogonal fluorescence probe method, based on 8‐anilinonaphthalene‐1‐sulfonate binding to partially unfolded states, resulted in very good agreement. In summary, our study highlights the validity of this easy‐to‐perform analysis for reliably assessing the kinetic stability of IgGs, which can support accelerated formulation development of monoclonal antibodies by ranking different formulations as well as by improving colloidal stability models.